2018
DOI: 10.1111/bjh.15462
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic ancestry profile of a large multi‐centre sickle cell disease cohort in Brazil

Abstract: Approximately 3500 children with sickle cell disease (SCD) are born in Brazil each year, but the burden of SCD morbidity is not fully characterised. A large, multi-centre cohort was established to characterise clinical outcomes in the Brazilian SCD population and create the infrastructure to perform genotype-phenotype association studies. Eligible patients were randomly selected from participating sites and recruited at routine visits. A biorepository of blood samples was created and comprehensive demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 22 publications
1
50
0
Order By: Relevance
“…While recruitment targeted high‐intensity donors and minority populations, including Asian, African American, and Hispanic donors, the US donor population most closely resembles this study population. Additionally, REDS‐III has also conducted a cohort study of 2798 patients with SCD from six hemocenters in Brazil who are being followed longitudinally . High‐quality DNA was obtained from both cohorts using white blood cells (WBCs) eluted from leukoreduced filters for the RBC‐Omics study and whole blood samples for the Brazil SCD cohort.…”
Section: Methodsmentioning
confidence: 99%
“…While recruitment targeted high‐intensity donors and minority populations, including Asian, African American, and Hispanic donors, the US donor population most closely resembles this study population. Additionally, REDS‐III has also conducted a cohort study of 2798 patients with SCD from six hemocenters in Brazil who are being followed longitudinally . High‐quality DNA was obtained from both cohorts using white blood cells (WBCs) eluted from leukoreduced filters for the RBC‐Omics study and whole blood samples for the Brazil SCD cohort.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the Recipient Epidemiology and Evaluation Donor Study (REDS)‐III Brazilian SCD cohort have been previously reported . Patients were randomly selected to be eligible for the REDS‐III cohort from the active SCD patient population (clinical visit within the past 3 years) at four transfusion centers in six cities in Brazil: HEMOPE (Recife); Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, Instituto da Criança (São Paulo); HEMORIO (Rio de Janeiro); and HEMOMINAS (Belo Horizonte, Juiz de Fora, and Montes Claros).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical and genetic ancestry profile of a large multicenter SCD cohort in Brazil. A description of patient recruitment and study procedures, and baseline data collected during enrollment visits (2013-2015) (Carneiro-Proietti et al, 2018). The article also reports the sequencing of single nucleotide polymorphisms (SNPs) covering the entire genome.…”
Section: Brazilmentioning
confidence: 99%